Non-representational marketing theory. (December 2014) - Hill, Tim; Canniford, Robin; Mol, Joeri
The purpose of this article is to evaluate and advance tools that marketing and consumer researchers have recently gathered from assemblage and actor–network theories. By distinguishing between two different styles of applying these theories we explain that a 'representational', interventionist and problem-solving mode has come to dominate existing uses of assemblage and actor-network theories in our field. We explain that current applications can be supplemented by a non-representational mode of theorising that draws on work pioneered by Nigel Thrift. Specifically, we explain that non-representational marketing theory can expand our ontological sensitivities through improved attention to the minutiae and hitherto unrepresented constituents of life. Towards this end, we offer methodological suggestions to extend attention to flows of everyday marketplace activity, precognitive forms of networked agency, as well as affect and atmosphere in consumption spaces.